She'll be coming around the mountain - Coplon, Emily; Orgel, Doris; Schecter, Ellen; Barnes-Murphy, Rowan (New York : Bantam Books, Inc., 1994)
This new version of the song "She'll Be Coming Round the Mountain" depicts a boisterous family celebration.
"A Byron Preiss book."
"Level 1 -- Preschool-Grade 1"
NP
Accelerated Reader AR
Keywords: Children's songs -- Texts; Songs